(untitled) (Journal of Association of Clinical Endocrinologist and Diabetologist of Bangladesh, 2025)
Carbimazole (CBZ) induced agranulocytosis is a rare but potentially life-threatening complication. The treatment of choice in this condition is definitive therapy like radioactive iodine (RAI) ablation or thyroidectomy. Prior to RAI ablation euthyroidism should be attained to lower the risk of thyroid function deterioration and treatment failure. A 19-year-old girl with Graves hyperthyroidism and a previous history of CBZ-induced agranulocytosis came for definitive management. She was treated with lithium, therapeutic plasma exchange, and cholestyramine with dexamethasone sequentially to render euthyroidism while awaiting elective RAI ablation. But none of these measures successfully normalized her thyroid function. Propylthiouracil (PTU) started with close monitoring and she became nearly euthyroid biochemically after about two weeks. RAI ablation was done after withholding PTU for five days. She became hypothyroid five months after RAI ablation and levothyroxine replacement started. This case highlights the challenges in treating hyperthyroidism prior to elective RAI ablation in a patient with CBZ-induced agranulocytosis. J Assoc Clin Endocrinol Diabetol Bangladesh, July 2023; 2 (2):75-78